Padrões estruturais da regeneração em áreas de pastagens e remanescentes de florestas estacionais deciduais no Parque Estadual do Pau Furado, MG - Macedo, Mariane Mendes (2016)
Among the phytophysiognomies of Cerrado biome lies the Decidual Seasonal Forest (DSF), degradation and fragmentation object in face of economic interests. This work aimed to assess natural regeneration on abandoned pasture areas and three DSF fragments located at Pau Furado State Park. There were sampled 10 plots in each location. Were calculated relative density estimations, relative frequency, Natural Regeneration Rate per Size Class (NRR), Shannon Diversity Index (H’) and Pielou Equability (J) for each species in each area. During natural regeneration of DSF fragments research it was observed presence of 25 families, 50 species, and 999 individuals. The Fabaceae family demonstrated larger density, followed by Cannabaceae and Myrtaceae. The species Piptadenia gonoacantha presented major density, then Celtis iguanaea and Campomanesia velutina. In Class I the species that exhibited larger NRR were Campomanesia velutina, Celtis iguanaea and Piptadenia gonoacantha, while in Class II were Piptadenia gonoacantha, Pouteria torta, Allophylus sericeus, Campomanesia velutina, Celtis iguanaea, Mimosa tenuiflora, Rollinia rugulosa. On pasture areas, considering natural regeneration Class I there were sampled 150 individuals, distributed in 06 (six) families, 12 (twelve) genres, and 13 (thirteen) species. The families that demonstrated larger density in Class I were Fabaceae and Asteraceae. The species with major relative density and NRR were Vernonanthura phosphorica, Chromolaena sp. and Myracrodruon urundeuva. In Class II, Senna sp. and Vernonanthura phosphorica exhibited greater NRR Piptadenia gonoacantha also demonstrated high NRR level on Semidecidual Seasonal Forest studies, and this species exercises important ecological function due to act on nitrogen fixing, as of symbiotic interaction. Celtis iguanaea besides being a pioneer species also demonstrated high importance index of DSF in Central Brazil. Senna sp. high density corroborates with other studies, which was the only species observed out of isolated trees canopies at abandoned pasture. The elevated NRR rate of Myracroduon urundeuva was also noted on abandoned pasture at Pau Furado State Park. It is recommended management and removal of invasive exotic grasses, with the purpose to stimulate development of native species with natural regeneration interest.